Gambaran Kualitas Fisik Air Dan Kualitas Fisik Pada Penampungan Air Hujan Di Desa Pempatan Kecamatan Rendang Kabupaten Karangasem Tahun 2025 - Ari Suryaningrat, I G A; Aryana, I Ketut; Sali, I Wayan; Aryasih, I G A Made (Poltekkes Kemenkes Denpasar, 2025)
Background: One alternative to fulfill clean water in areas that have not been reached by piped networks is through Rainwater Reservoirs.Method: Total of 96 samples were examined using temperature, TDS, turbidity, color, odor, parameters.Result: The results showed that all samples met the requirements for temperature and TDS. 51 (53.1%) samples did not meet the requirements for turbidity and color, while 10 (10.4%) showed an odor that did not meet clean water standards. Most of the reservoirs, 94 (97.9%) were contaminated by dirt from the roof, and all gutters were dirty.Conclusion: it is necessary to improve Rainwater Reservoirs facilities to ensure safe water quality for the community